Pengembangan Aplikasi Animasi Kinemaster Sebagai Media Pembelajaran Interaktif Bagi Guru SD Negeri Pakuan - Ni Made Widisanti; Dyah Kristyowati; Resty Widya Kurniasari (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The research results are to develop the KineMaster application to create an interactive learning media for Pakuan State Elementary School teachers. Research design uses a descriptive quantitative approach with data collection techniques through questionnaires and interviews. The results of the study have obtained the need for interesting and interactive learning media, students have difficulty consulting with teachers, especially for lessons that are considered to require deeper explanation and understanding. To overcome this, the use of learning media using the KineMaster application can be a very easy and effective alternative for teachers in carrying out learning. During the covid-19 pandemic, this application can be a solution for teachers in replacing teachers’ conventional classroom methods in the room. Kinemaster application presents a fairly simple look, but stores quite complex features. This condition can help students in understanding the learning materials. Creating learning media through animated videos using the KineMaster application is quite easy. Thus, Kinemaster applications can be used in developing materials and teaching materials for elementary teachers.